Structure, diversity and carbon estimation of an ecoton between tamaulipan and submontane thorny scrub - Carranza-Guerrero, Ana Karen; Alanís-Rodríguez, Eduardo; Patiño-Flores, Ana María; Mora-Olivo, Arturo; Molina-Guerra, Víctor Manuel (Ecosistemas y Recursos Agropecuarios, 2024)
The ecotone is of great importance given the environmental services they provide both to the environment and to human wellbeing. The objective was to know the structure and floristic composition of a contact zone between two types of bushes and also to know the potential it has as a carbon sink. Importance value indices, vertical species distribution, Margalef, Shannon, and true Shannon diversity, as well as biomass, total area, and carbon concentration were determined. Eleven species of vascular plants were recorded, the best represented family was Fabaceae and Cordia boisieri was the species with the highest importance value index. The diversity of the plant community is low according to the Shannon index. The total canopy area was 4 276.03 m2 ha-1, while the vertical index of species defined three height strata. The stored carbon is 2.82 Mg ha-1, while the total aerial biomass was 5 667.15 kg ha-1.
Keywords: composition, disturbance, floristics, transition, vegetation